Bacillus subtilis as a potent probiotic for enhancing growth in fingerlings of common carp (Cyprinus carpio L.) - Bisht, Akansha; Singh, Uday Pratap; Pandey, Nityanand (Indian Journal of Fisheries, 2012)
A feeding trial of 180 days was conducted to examine the effect of Bacillus subtilis, a probiotic bacterial strain isolated fromthe gut of common carp, on weight gain and growth performance in fingerlings of common carp. Three isonitrogenous dietswere prepared and B. subtilis was incorporated in the experimental diets, D2 and D3 at two different levels viz.,4 x 106 and4 x 108 cells per 100 g of feed, respectively along with a control diet D1 without incorporation of probiotic. Rearing offingerlings on diet D3 (supplemented with 4 x 108 cells per 100 g) resulted in better growth, specifit growth rate (SGR), feedconvertion ratio (FCR), feed convertion efficiency (FCE) and condition factor compared to D1 and D2. IncreasedRNA-DNA ratios were recorded in probiotic fed group with best result for D3. The results clearly indicate that B. subtilis canbe used as a growth promoting probiotic in the diet of common carp fingerlings.